Strategi Marketing Public Relations Mischief Denim di Masa Pandemi - Tamareisya Setiawan Putri; Maman Chatamallah (Bandung Conference Series: Public Relations, 2022)
Abstract. The presence of the Covid-19 pandemic crisis has affected Mischief Denim as one of the business sector. In this regard, the activities of a company must continue to run with the role of marketing public relations in it so that they can then maintain their business. Like Mischief Denim did with the “photo contest challenge” program as a marketing public relations program. This study aims to determine the planning, implementation, and reasons for Mischief Denim choosing the “photo contest challenge” program as a marketing public relations strategy during the pandemic. The research method used is a qualitative method with a case study approach. The theory used in this research is marketing public relations, the concept of a three-way strategy, and the concept of the operational process of public relations. Data collection techniques were conducted by interview, observation, literature study and documentation. While the subjects interviewed in this study amounted to two people from the Mischief Denim. The results of this study found that Mischief Denim's marketing public relations strategy planning through the "photo contest challenge" program during the pandemic was carried out by brainstorming by several divisions to negotiate several points, such as what program was made and its targets, determination of themes, objectives of the program, determine budget, and preparing rules and visual output in the form of content for Mischief Denim's Instagram social media. In its implementation, it is in accordance with the stages that have been planned, although there are obstacles but can be overcome. Meanwhile, the reason Mischief Denim chose the "photo contest challenge" program as a marketing public relations strategy during the pandemic was to do brand activation, increase awareness, and reduce costs. Abstrak. Hadirnya krisis pandemi Covid-19 membuat Mischief Denim sebagai salah satu sektor bisnis ikut terdampak. Sehubungan dengan hal tersebut, kegiatan suatu perusahaan harus tetap berjalan dengan peran marketing public relations di dalamnya untuk kemudian dapat mempertahankan bisnisnya. Seperti halnya yang dilakukan oleh Mischief Denim dengan adanya program “photo contest challenge” sebagai program marketing public relationsnya. Penelitian ini bertujuan untuk mengetahui perencanaan, implementasi, dan alasan Mischief Denim memilih program “photo contest challenge” sebagai strategi marketing public relations di masa pandemi. Metode penelitian yang digunakan yaitu metode kualitatif dengan pendekatan studi kasus. Teori yang digunakan dalam penelitian ini adalah marketing public relations, konsep three ways strategy, dan konsep proses operasional public relations. Teknik pengumpulan data dilakukan dengan wawancara, observasi, studi kepustakaan dan dokumentasi. Sedangkan subjek yang diwawancarai dalam penelitian ini berjumlah dua orang dari pihak Mischief Denim. Hasil dari penelitian ini yaitu ditemukan bahwa perencanaan strategi marketing public relations Mischief Denim melalui program “photo contest challenge” di masa pandemi, dilakukan dengan brainstorming oleh beberapa divisi untuk merundingkan beberapa poin, seperti program apa yang dibuat dan sasarannya, penentuan tema, tujuan dari program yang dibuat, penentuan anggaran, serta mempersiapkan rules dan output visual berupa konten untuk media sosial instagram Mischief Denim. Pada implementasinya sudah sesuai dengan tahapan yang telah direncanakan, walaupun sempat terkendala namun bisa diatasi. Sedangkan alasan Mischief Denim memilih program “photo contest challenge” sebagai strategi marketing public relations di masa pandemi adalah untuk melakukan brand activation, meningkatkan awareness, serta biaya yang lebih murah.